Design of a high-speed optical wireless LAN at long wavelengths - Zyambo, E; O'Brien, D; Faulkner, G; Edwards, D (2001)
In the design of infrared wireless networks, it is often assumed that the noise from the detector and preamplifier is much lower than that from ambient light sources and hence can be ignored in performance analysis calculations. However, in cellular tracked networks, where the fields of view (FOV) are narrow, the contribution of the noise from the ambient light sources is greatly reduced and the detector and preamplifier noise become a dominant noise source. An optical system and preamplifier model is used to predict the performance of a single channel indoor wireless link operating in this regime. Simulations predict a single 10mW source can provide 1Gbit/s wireless coverage over a cell 0.4m in diameter at a distance of 2m from the source. Further, overall link performance is found to be relatively insensitive to photodetector capacitance.